2010
DOI: 10.1590/s0034-76122010000400009
|View full text |Cite
|
Sign up to set email alerts
|

Informações de custos e qualidade do gasto público: lições da experiência internacional

Abstract: Su m á r i o : 1. Introdução; 2. A importância de informações sobre custos para a melhoria da qualidade do gasto público; 3. Motivações e objetivos para a adoção de regimes contábeis que gerem informações sobre os custos do governo; 4. A adoção da contabilidade de competência deve levar necessariamente à adoção também de um orçamento de competência?; 5. O debate atual: da informação à decisão; 6. A experiência internacional e as diretrizes para adoção de um sistema de custos no setor público brasileiro; 7. Sín… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1
20

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 7 publications
0
5
1
20
Order By: Relevance
“…Seeking to improve the efficiency and performance in the public administration, one saw the need to get real information on the costs arising from government actions (Rezende, Cunha & Bevilacqua, 2010). Xavier Queiroz, and Miranda (2013) complement that, with the coordination of human, material resources and assets, to the needs presented by the society, it is clear the need to search for efficiency, efficacy and effectiveness in the use of public resources.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Seeking to improve the efficiency and performance in the public administration, one saw the need to get real information on the costs arising from government actions (Rezende, Cunha & Bevilacqua, 2010). Xavier Queiroz, and Miranda (2013) complement that, with the coordination of human, material resources and assets, to the needs presented by the society, it is clear the need to search for efficiency, efficacy and effectiveness in the use of public resources.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Borges et al (2010) destacam que o regime de competência promove "uma melhoria na qualidade da informação para a decisão e gera incentivos aos gestores públicos para melhor utilizar o recurso e aumentar a transparência". Através do regime de competência, os custos são reconhecidos no momento em que ocorrem, com base no capital efetivamente consumido no ano (Rezende, Cunha & Bevilacqua, 2010). A apuração dos custos de depreciação, exaustão ou amortização possibilita melhorar o planejamento, pois o impacto orçamentário financeiro terá reflexo tanto no exercício atual quanto nos subsequentes (Silva, 2009).…”
Section: Depreciação Amortização E Exaustãounclassified
“…It adds further that it is necessary for public sector managers know the activities costs in order to make better management decisions, such as deciding to produce or buy. Between national research related to public cost management, it is observed that there is a questioning in the studies on the efficiency of public spending, this fact can be observed in the studies of Machado and Holanda (2010), Magalhães et al (2010), Rezende, Cunha and Bevilacqua (2010), Cavalcante and Lariu (2012), Borges, Mario and Carneiro (2013), Couto and Coelho (2015).…”
Section: Introductionmentioning
confidence: 99%